Analysis of Factors Contributing to Establishment and Development of Business in Lithuanian Regions - Šneiderienė, Agnė (Socialiniai tyrimai, 2018)
Nowadays, when economies are changing in a rapid speed, state borders are weakening, regions underpin and form larger units. In such situation, human resources and the accumulated knowledge become one of the factors determining the creation and development of business in the regions, that play an important role in regional economic growth. It should be emphasized that the creation and development of business in the regions depend not only on the implementation of the ideas of entrepreneurs themselves, the quality of human resources, technologies and innovations in the regions, but also on cooperation between business, self-government and educational institutions. According to Laužikas et al. (2014), it is not enough of person’s qualifications, professional knowledge and experience when we consider larger business opportunities. Business and its system exist in a particular environment in which different processes occur, and entrepreneurship to large extent depends on the ways in which individuals are encouraged to take business. Promotion of entrepreneurship is related to the interpretation, promotion and dissemination of business knowledge in a society and offering appropriate forms of support to create private business. It is noted that various levels of government in the European Union, national, regional or local authorities carry out various activities that promote people’s initiative, entrepreneurship and business development. Therefore, it is very important to determine what support instruments promote the creation and development of business in the regions of Lithuania.The object of the research is the support instruments that promote business creation and development.The aim of the article is to determine what support instruments promote the creation and development of business in the regions of Lithuania.To achieve the aim, the following tasks have been formulated:1. To analyse the theoretical aspects of the influence of entrepreneurship on economic growth in the region.2. To evaluate business development trends in the regions of Lithuania.3. To investigate business development and development support instruments in Lithuanian regions.The scientific literature analysis, statistical analysis, and descriptive, analytical and comparative analysis methods have been employed for the research.In order to evaluate the situation of business creation and development in the regions of Lithuania, the analysis is carried out at two levels, i.e. the number of selected business indicators (the number of small and medium sized enterprises operating at the beginning of the year, the number of legal entities registered in the year, the number of registered enterprises per year, the number of persons who obtained business licenses, the number of small and medium size enterprises per 1000 inhabitants at the beginning of the year) are investigated in the territory of Lithuania which is divided into 2 regions: Capital and Central and West Lithuanian region; these indicators are also investigated in Lithuanian regions which are defined as counties.The ability of the region to provide a better standard of living for its people critically depends on the longterm economic growth rate. In the long run, even a small difference in economic growth rates between regions can turn into a large difference in average human incomes. In addition, the factors that determine the economic growth of most regions can also be linked to their impact on business creation and development in the regions, as entrepreneurship is an important precondition for regional growth and development.After analysing the indicators reflecting the creation and development of business in the regions of Lithuania, it can be stated that Capital region is the leader according to the following indicators: the number of new legal entities registered per year, the number of small and medium-sized enterprises registered per year, and the number of small and medium-sized enterprises operating per 1000 inhabitants. The region of Central and Western Lithuania is the leader according to the following indicators: the number of unregistered legal entities at the beginning of the year, the number of legal entities registered annually, the number of small and mediumsized enterprises registered annually, the number of small and medium-sized enterprises at the beginning of the year, and the number of persons who obtained business licenses. It should be emphasized, that significant differences exist when the analysis of counties forming the region of Central and Western Lithuania is conducted. Kaunas and Klaipėda counties prevail, while Telšiai and Utena counties are behind other Lithuanian regions according to many indicators.In the municipalities of the regions of Lithuania, a lot of attention is devoted to support the process of business creation and development. Business creation and development are encouraged by offsetting start-up costs, preparation of a business plan or project, reimbursement cost of interest or new job creation and training, and encouraging participation in exhibitions, fairs or business missions. It should be emphasized that only the amount of support is different in these municipalities of Lithuanian regions.
Keywords: entrepreneurship; business support; region; regional economic growth